The MARRIAGE MOVING THROUGH THE INTERMEDIATE TRUST AGENT IN SOUTHERN THAILAND - Ibrorheng Dorloh; Alias Azhar, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2016)
Islam is a religion that regulates the affairs of human life, whether business world and hereafter. He arranges all aspects of life and human needs. None, and small business and the needs of human life on earth is spared from the teachings of Islam. The importance of marriage in Islam is a nature or purpose of life such as the desire to have children and families. In order to ensure the continuity and the marriage of a position to meet the law, the Islamic scholar underlined a number of conditions and harmonious marriage in their books. The existence of a trustee, for example, is one of the pillars of marriage which is an important guardian role in arranging the marriage relationship even though on the face of the trustee representing the woman under his care, but in fact more than that in which it has the power to determine and to represent anyone who was under his care , This paper is a paper that discusses the concept of marriage guardian moved through agents conducted by some in South Thailand which were done by the people of the neighboring countries and adjacent to Thailand.